Screening and characterization of Bacillus velezensis LB-Y-1 toward selection as a potential probiotic for poultry with multi-enzyme production property - Li, Chong; Li, Shuzhen; Dang, Guoqi; Jia, Rui; Chen, Si; Deng, Xuejuan; Liu, Guohua; Beckers, Yves; Cai, Huiyi (Frontiers in Microbiology, 2023)
Bacillus spp. have gained increasing recognition as an option to use as antimicrobial growth promoters, which are characterized by producing various enzymes and antimicrobial compounds. The present study was undertaken to screen and evaluate a Bacillus strain with the multi-enzyme production property for poultry production. LB-Y-1, screened from the intestines of healthy animals, was revealed to be a Bacillus velezensis by the morphological, biochemical, and molecular characterization. The strain was screened out by a specific screening program, possessed excellent multi-enzyme production potential, including protease, cellulase and phytase. Moreover, the strain also exhibited amylolytic and lipolytic activity in vitro. The dietary LB-Y-1 supplementation improved growth performance and tibia mineralization in chicken broilers, and increased serum albumin and serum total protein at 21 d of age (P < 0.05). Besides, LB-Y-1 enhanced the activity of serum alkaline phosphatase and digestive enzyme in broilers at 21 and 42 d of age (P < 0.05). Analysis of intestinal microbiota showed that a higher community richness (Chao1 index) and diversity (Shannon index) in the LB-Y-1 supplemented compared with the CON group. PCoA analysis showed that the community composition and structure were distinctly different between the CON and LB-Y-1 group. The beneficial genera such as Parasutterella and Rikenellaceae were abundant, while the opportunistic pathogen such as Escherichia-Shigella were reduced in the LB-Y-1 supplemented group (P < 0.05). Collectively, LB-Y-1 can be considered as a potential strain for further utilization in direct-fed microbial or starter culture for fermentation.